Manajemen Anestesi pada Pasien dengan Malformasi Arnold-Chiari tipe I dan Siringomielia - Pratomo, Bhirowo Yudo; Widyastuti, Yunita; Ngahu, Robby Mesakh (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2019)
Arnold–Chiari malformation (ACM) type I in syringomyelia patients can present with autonomic dysfunction.Anesthesia management requires careful preoperative assessment, precise identification of potential problems, and appropriate planning. We present a case report of a 29 years-old woman diagnosed with ACM type I with siringomielia associated with autonomic dysfunction. The patient was underwent suboccipital decompressive craniotomy. Patient exhibited symptoms of weakness in her upper limbs since 3 years ago, unable to hold items, paresthesia, and gradually progressed loss of temperature and pain sensation. Routine preoperative investigation were within normal limits. After intubation, the patient was placed in prone position. Thus, patient had hypotension with tachycardia, managed with intravenous (IV) fluid and vassopressor. During surgery the patient experiences instability of hemodynamics profile.